Review articleFeasibility of functional imaging for brachytherapy - Polo, Alfredo (Journal of Contemporary Brachytherapy, 2009)
This review summarizes the current understanding of the feasibility of functional imaging for brachytherapy. In following subsections the role of ultrasound, power doppler imaging, positron emission tomography, magnetic resonance imaging, dynamic dose calculation and targeted brachytherapy is analyzed. The combination of functional imaging with the new tools for intraoperative dose calculation and optimization opens new and exciting times in brachytherapy. New optimized protocols are needed and should be tested in controlled trials, to demonstrate an advantage of such a new paradigm.